2001
DOI: 10.1093/qjmed/94.8.407
|View full text |Cite
|
Sign up to set email alerts
|

Lung involvement and enzyme replacement therapy in Gaucher's disease

Abstract: Symptomatic lung involvement in Gaucher's disease is relatively rare, being restricted to patients with other severe manifestations. We describe our experience in eight of 411 patients in our referral clinic, who presented with prominent pulmonary signs or symptoms. There were four adults and four children; all have been successfully treated with enzyme replacement therapy. Routine means of monitoring pulmonary status including clinical assessment, chest X-ray, pulmonary function tests, and high-resolution CT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 21 publications
0
46
0
4
Order By: Relevance
“…Type 1 GD patients respond well to ERT [30] with improvement of hepatosplenomegaly and hematological parameters as well as increased well-being [31] . Nevertheless, there is a wide heterogeneity in the response of pulmonary manifestations to ERT [30] . Schiffmann et al [32] reported that miglustat in combination with ERT may have positive effects by improving pulmonary function.…”
Section: Disorders Involving Complex Moleculesmentioning
confidence: 99%
“…Type 1 GD patients respond well to ERT [30] with improvement of hepatosplenomegaly and hematological parameters as well as increased well-being [31] . Nevertheless, there is a wide heterogeneity in the response of pulmonary manifestations to ERT [30] . Schiffmann et al [32] reported that miglustat in combination with ERT may have positive effects by improving pulmonary function.…”
Section: Disorders Involving Complex Moleculesmentioning
confidence: 99%
“…Zwei therapeutische Ansätze stehen zur Verfügung: 1. eine ERT mit rekombinanter humaner Glucocerebrosidase oder 2. die Substratreduktionstherapie mit Miglustat. Patienten mit M. Gaucher Typ 1 sprechen gut auf eine ERT [30] an und zeigen eine Besserung der Hepatosplenomegalie, der hämatologischen Parameter und des Wohlbefindens [31]. Die pulmonalen Manifestationen sprechen allerdings sehr unterschiedlich auf eine ERT an [30].…”
Section: Morbus Gaucherunclassified
“…Patienten mit M. Gaucher Typ 1 sprechen gut auf eine ERT [30] an und zeigen eine Besserung der Hepatosplenomegalie, der hämatologischen Parameter und des Wohlbefindens [31]. Die pulmonalen Manifestationen sprechen allerdings sehr unterschiedlich auf eine ERT an [30]. Schiffmann et al [32] berichteten, dass die Kombinationstherapie von Miglustat und ERT positive Effekte haben kann, da sie die Lungenfunktion verbessert.…”
Section: Morbus Gaucherunclassified
“…GBA1 mutations may alter GCase stability and/or impair its catalytic function. 37,38 The identification of disease-causing mutations in GBA1 may be challenging due to the GBAP. The most accurate method for mutation analysis in GD is full-gene sequencing of GBA1.…”
Section: Diagnosismentioning
confidence: 99%